The Liberalization process of the Ferry System in Greece, 2001-2014 (August): What are the benefits to users of Aegean Sea Transportation? - Alexandros M. Goulielmos; Ioannis M. Sitzimis (SPOUDAI - Journal of Economics and Business, 2014)
The great deficits created in the pursuit of the Keynesian welfare state led to governmental failure. This increasingly posed a greater risk to financial system than market failure, due to the increasing scale effects. Competition ceases to exist. The operations of markets first described by Adam Smith (1776) and confirmed by Alfred Marshall (1920). As a result of the increasing risk of governmental failure, legal barriers to "entry" removed (liberalization) and private ownership promoted (privatization). Here, we investigate the impact of the "liberalization processes of (private)" "Aegean Ferry System" since 2001, and look at the effect on passenger fares and private cars freight rates under "free entry". Quality of service was never regulated…We showed the existence of increasing returns to scale in the ferry system and in the individual ship, basing our arguments on empirical data and on theory. The fixed cost of the ferry system is 68%, indicating failure of the ferry market, when prices had to be determined by marginal cost leading to operational losses, since average cost is twice greater than marginal cost. Despite the hopes of the users that Greek Aegean ferry system's liberalization would lead to reduction in fares and freight rates, this did not happen. Reforms paralleled those in air transport in USA, and a similar "hub and spoke" network system proposed and adopted careless by Greece, following the study. Fares and private car freight rates rose in a series of waves, owners frequently blaming the rising oil prices…
Keywords: D4; L1; R49; 330; Liberalization of the Greek Aegean Ferry system; Fares and freight rates; increasing returns to scale